An integrated archeomagnetic and C14 study on pre‐Columbian potsherds and associated charcoals intercalated between Holocene lacustrine sediments in Western Mexico: Geomagnetic implications. Issue 6 (28th June 2013) - Aguilar Reyes, B.; Goguitchaichvili, A.; Morales, J.; Garduño, V. H.; Pineda, M.; Carvallo, C.; Moran, Tomas González; Israde, Isabel; Rathert, Manuel Calvo
Abstract : [1] The firm relationship between archeomagnetic samples and their absolute ages, which is usually determined or estimated using a variety of methods (archaeological context, thermoluminiscense, C 14, etc.), is crucial in any archaeomagnetic investigation. In this paper, we report 18 successful (from 65 analyzed) archaeointensity determinations of high technical quality performed on specimens obtained from three fragments of pre‐Columbian potsherds. These are unambiguously correlated with charcoal samples, as they were found together in three thin lacustrine sedimentary layers in western Mexico. Moreover, new radiometric results were obtained in this study from all charcoal samples (beta analytic) yielding ages of 1490 ± 40, 1510 ± 40, and 1580 ± 40 BP. In addition, detailed magnetic measurements were carried out on all studied ceramic fragments. These rock magnetic experiments, which included low field susceptibility versus temperature, hysteresis, and first‐order reversal curve measurements, indicate that the main magnetic carrier is Ti‐poor titanomagnetite. The average archeointensity values per ceramic fragments obtained in this study are very similar in all three cases: 35.2 ± 1.3 μT ( N  = 5), 36.8 ± 1.6 μT ( N  = 6), and 37.2 ± 3.4 μT ( N  = 7). This corresponds to an average intensity of 36.4 ± 1.1 μT and a virtual axial dipole moment value of 8.1 ± 0.2 × 10 22 Am 2, which is slightly lower than the present field strength, corresponding at an age interval between 640 and 430 A.D. Although we detected some relationship between the Earth's magnetic field intensity and multidecadal climatic events, such observations can only be considered tentative at this stage. Key Points: Relationship between archeointensity and climate Absolute Geomagnetic Intensity Variation over the last 2 Milenia Archeomagnetic reference curve for Mesoamerica